Resolution on the results of the expert council on the topic “Diagnosis and treatment of advanced non-small cell lung cancer with BRAF mutation: from the search for molecular targets to therapeutic strategies in real-world clinical practice” - K. K. Laktionov; V. V. Breder; I. A. Demidova; V. V. Karaseva; F. V. Moiseenko; S. V. Orlov; E. V. Reutova; D. L. Stroyakovsky (Malignant tumours, 2026)
On January 27, 2026, an Advisory Board was held to discuss issues of molecular genetic diagnosis of the BRAF V600E mutation in patients with advanced non-small cell lung cancer (NSCLC), as well as current treatment options for NSCLC patients with the BRAF V600E mutation. Next generation sequencing (NGS) is the most sensitive and specific method for molecular genetic testing. Its implementation in routine clinical practice will improve the detection rate of BRAF positive NSCLC patients. The accepted standard of care for patients with advanced NSCLC and the BRAF V600E mutation is targeted therapy with BRAF / MEK inhibitors. In the Russian Federation, the combination of dabrafenib and trametinib is approved for use. At the Advisory Board, results were presented from a study of a new targeted combination: encorafenib (a BRAF inhibitor) and binimetinib (a MEK inhibitor). In the Phase II PHAROS clinical trial, the encorafenib — binimetinib combination demonstrated a high rate and durability of antitumor response in adult patients with advanced NSCLC and the BRAF V600E mutation. The objective response rate in treatment naive and previously treated patient groups was 75 % and 49 %, respectively. The median progression free survival (PFS) in the subgroups was 30.4 months and 9.3 months, respectively. At the time of publication, the indication “advanced NSCLC with the BRAF V600E mutation” for the targeted drug combination of encorafenib and binimetinib has not been registered in the Russian Federation.